The Role of the Indian Judiciary to Combat Sexual Abuse Against Children - Ghosh , Rajdeep (International Journal of Psychosocial Rehabilitation, 2019)
India is reckoned as the home of about 19 percent of children in the world. Many reports of many authorities including the Census of 2011 depict that more than one-third of India’s total population are children i.e., below eighteen years of age. As per one assumption, more than forty percent of these children are in need of care and protection which showcases the gravity of the problem at hand. India has taken several steps and measures to address and redress the issues relating to children in India which include child education, child health, and child development. But Child protection has remained an issue before and even after the enactment of special child laws like the Protection of Children from Sexual Offences Act of 2012 and Juvenile Justice (Care and Protection of Children) Act, 2015, and these issues are addressed by the judiciary from time to time. Abuse of children has been shrouded in an environment of secrecy which signifies a conspiracy of silence around the entire subject matter of the same.i This article endeavors to highlight the role of the Indian Judiciary to combat sexual abuse against children through judicial activism or through interpretation of the existing provisions of law depending on the ratio decidendi or rationale of a few leading and landmark cases along with providing a few guideposts.